A Bibliometric Study of Papers Published in Library and Information Science Research during 1994 2020 - Garg, K. C.; Singh, Rahul Kumar (DESIDOC journal of library & information technology, 2022)
The paper analysed 699 papers published in Library & Information Science Research (LISR) during the period of 1994-2020. Google Scholar was used to obtain the number of citations received by these papers until April 30, 2021. The study examined the geographical distribution of published articles and also identified prolific institutions and authors. The study examined the impact of output of countries, institutions and authors using citation per paper (CPP) and i-10 index as indicators of impact. The study also examined the pattern of growth and identified the highly cited papers. Based on the analysis of data it is observed that maximum articles were published during the three years block of 2015-2017. The geographical distribution of output indicates that 51 countries contributed the 699 papers. Highest number of papers was contributed by authors from the USA though it had a low value of CPP in comparison to Norway and Finland. Among the institutions, Florida State University (USA) topped the list. However, University of Illinois at Urbana-Champaign, USA had the highest value of CPP. During the period of study, 1,389 papers received 74,061 citations, of which only 41 (3 %) articles remained uncited.